EXPERIMENTAL FLEXURAL STRENGTH OF GLASS FIBER REINFORCED POLYMER (GFRP) HYBRID REINFORCED CONCRETE BEAMS - Lestyowati, Yoke; Herawati, Henny; Panandita, Budi Satria (Jurnal Teknik Sipil, 2023)
Materials technology is an excellent opportunity to be developed industrially and on a needs scale according to the demands of society, namely supporting the environment, low maintenance, and long-term use. Using composite materials with reinforced polymers is a hot topic of discussion in civil engineering as new materials, strength/stiffness enhancers, or applications in building rehabilitation or renovation. Fiber Reinforced Polymer (FRP) is excellent as a new material because, in addition to being lightweight, corrosion resistant, and easy to work with, it also has high flexural strength, so it is a consideration to replace and or strengthen steel materials that are high in cost value. However, until now there has not been found the correct pattern or variant and volume of fibre so that it can be an alternative to the use of steel. The purpose of the study was to experimentally determine the flexural strength of Glass Fiber Reinforced Polymer (GFRP) hybrid beams either with steel reinforcement, with GFRP reinforcement, or with steel and GFRP combination reinforcement and different GFRP ratios (variants) through two-point load bending tests.The designed model is a development of a previous study that used one layer of 4 mm and produced a flexural strength smaller than the targeted flexural strength, so in this study, two layers of 8 mm were used. In addition, other experimental data that has been carried out from the literature is also used where the results of parametric studies provide evidence of the positive effect of hybrid steel and GFRP reinforcement ratios when obtaining GFRP models and volumes.The materials used to manufacture concrete beam test specimens 53x15x15 cm3 with quality of fc'35MPa have been tested according to SNI standards and meet both the minimum and maximum requirements specified. Based on the results of the material test, it is planned that the characteristic concrete quality fcr'=40.31 MPa, and based on the compressive strength test, the quality fcr'=41.68MPa is produced.The hybrid designed material with concrete or concrete and steel has been tensile tested with a maximum arcing load for the two layers = 8 mm variant; the tensile strength of the GFRP woven roving type with two layers 2 x 4 mm is 92.66 MPa. While plain steel reinforcement Diameter 8mm quality 280 MPa has a minimum tensile strength of 350 MPa (3.8 times the tensile strength of GFRP 8 mm).The results of testing and calculating the effect of GFRP as a substitute for steel reinforcement contributed to the flexural strength of concrete beams on average by 47.52%. In comparison, the contribution of flexural strength produced by concrete with steel reinforcement was 107.09%. The concrete variant of hybrid steel reinforcement and GFRP contributes to an increase in the average flexural strength of 117.02% 4.8% compared to steel-reinforced concrete beams alone.